MTHFR C677T, Prothrombin G20210A, and Factor V Leiden (G1691A) Polymorphism and Beta-Thalassemia Risk: A Meta-Analysis - Nigam, Nitu (Cureus, 2020)
Background Beta (β)-thalassemia major patients frequently suffer from many vascular problems. Thrombophilia is a blood disorder that comprises imbalances in the blood coagulating factor due to ecological and hereditary components. Previous evidence shows that thrombosis is the commonest risk in beta-thalassemia patients. Several studies have examined that MTHFR C677T, prothrombin G20210A (PT G20210A), and Factor V Leiden G1691A (FVL G1691A) polymorphism play a crucial role in the development of β-thalassemia major, yet the result was questionable and uncertain. Therefore, in this study, we executed the correlation between these gene polymorphisms with β-thalassemia major patients. Methods Suitable keywords were used to search related articles in PubMed, Google Scholar, and Web of Science. In this random-effects meta-analysis, we analyzed the odds ratio (OR) for the estimation of risk. Results A total of nine research articles with 645 β-thalassemia major patients and 989 healthy controls were incorporated in this meta-analysis. The pooled OR was assessed in MTHFR C677T, PT G20210A, and FVL G1691A polymorphism. This random-effects meta-analysis demonstrated that MTHFR C677T, PT G20210A, and FVL G1691A gene polymorphism did not significantly associate with β-thalassemia major. Moreover, the heterogeneity was significantly found in genotype CC vs CT+TT C677T (I(2)=61%) and allele C vs T (I(2)=71%) of MTHFR and genotype GG vs GA (I(2)=95%), GG vs GA+AA (I(2)=95%), GA vs GG+AA (I(2)=95%), and allele G vs A (I(2)=93%) of FVL G1691A. Conclusion The results of this meta-analysis show that MTHFR C677T, prothrombin G20210A, and Factor V Leiden (G1691A) gene polymorphism are not a risk factor for β-thalassemia major.